2020
DOI: 10.1177/1091581820918163
|View full text |Cite
|
Sign up to set email alerts
|

Mesalazine Induces Oxidative Stress and Cytochrome c Release in Isolated Rat Heart Mitochondria: An Analysis of Cardiotoxic Effects

Abstract: Mesalazine is widely used in the management of inflammatory bowel disease. Previous studies reported that mesalazine-induced cardiotoxicity is a rare, potentially fatal complication. Mitochondria play an important role in myocardial tissue homeostasis. Deterioration in mitochondrial function will eventually lead to cardiomyocyte death and consequently cardiovascular dysfunction. The aim of the current study was to investigate the effects of mesalazine on rat heart mitochondria. Rat heart mitochondria were isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Analysis of the renal mitochondria showed decreased succinate dehydrogenase activity, mitochondrial swelling, mitochondrial depolarization and increased mitochondrial ROS [102]. Similarly, in the second study, the authors observed decreased succinate dehydrogenase activity, increased mitochondrial ROS, mitochondrial swelling and mitochondrial depolarization in hearts from mesalazinetreated rats [103].…”
Section: Interaction With Drugsmentioning
confidence: 82%
See 1 more Smart Citation
“…Analysis of the renal mitochondria showed decreased succinate dehydrogenase activity, mitochondrial swelling, mitochondrial depolarization and increased mitochondrial ROS [102]. Similarly, in the second study, the authors observed decreased succinate dehydrogenase activity, increased mitochondrial ROS, mitochondrial swelling and mitochondrial depolarization in hearts from mesalazinetreated rats [103].…”
Section: Interaction With Drugsmentioning
confidence: 82%
“…Different drugs (nonspecific or IBD-targeted therapies) have effects on mitochondrial function, which may not only have an impact on disease course, but also predispose treated patients to potential side-effects of the drugs. For instance, both sulfasalazine [102] and mesalazine [103] side-effects on renal injury and cardiotoxicity, respectively, have been related to their effects on mitochondrial function in these tissues. In the first study, kidneys from sulfasalazine-treated rats showed increased oxidative stress (increased ROS and lipid peroxidation and depleted glutathione reservoir).…”
Section: Interaction With Drugsmentioning
confidence: 99%
“…In addition, mesalazine induces reactive oxygen species formation and the mitochondrial membrane potential collapse in rat cardiac mitochondria. This causes mitochondrial dysfunction and cytochrome c release, eventually leading to cardiomyocyte apoptosis and cardiovascular dysfunction ( Salimi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been suggested that compounds such as melatonin can prevent cardiolipin peroxidation and protect mitochondria from excessive exposure to overload and limit reperfusion injury in the heart [ 47 ]. Another recent study has indicated the underlying mechanism of mesalazine resulting in cardiotoxic effect seems to relate to cytochrome c release, which means that mesalazine induces ROS formation leading to mitochondrial swell, mitochondrial membrane permeabilize, cytochrome c release, and eventual cardiomyocyte apoptosis [ 48 ]. However, as this study was conducted in isolated mitochondria, further studies in cells, animals, and clinical trials are still required.…”
Section: Oxidative Stress and Mitochondria-dependent Cardiomyocyte Ap...mentioning
confidence: 99%